2023
DOI: 10.1002/advs.202204794
|View full text |Cite
|
Sign up to set email alerts
|

H3K4 Methylation Promotes Expression of Mitochondrial Dynamics Regulators to Ensure Oocyte Quality in Mice

Abstract: Significantly decreased H3K4 methylation in oocytes from aged mice indicates the important roles of H3K4 methylation in female reproduction. However, how H3K4 methylation regulates oocyte development remains largely unexplored. In this study, it is demonstrated that oocyte‐specific expression of dominant negative mutant H3.3‐K4M led to a decrease of the level of H3K4 methylation in mouse oocytes, resulting in reduced transcriptional activity and increased DNA methylation in oocytes, disturbed oocyte developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…m6A may have a significant role in regulating chicken ovarian development. It has been reported that a decrease in H3K4 methylation levels can reduce transcriptional activity and increase DNA methylation in oocyte cells ( Jia et al, 2023 ), thereby interfering with their developmental potential and female fertility capacity ( Mei et al, 2023 ). We observed that candidate genes in the QYMC strain are enriched in the Wnt pathway and JNK pathway, which are important pathways regulating melanin production ( Liu et al, 2002 ; Yun et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…m6A may have a significant role in regulating chicken ovarian development. It has been reported that a decrease in H3K4 methylation levels can reduce transcriptional activity and increase DNA methylation in oocyte cells ( Jia et al, 2023 ), thereby interfering with their developmental potential and female fertility capacity ( Mei et al, 2023 ). We observed that candidate genes in the QYMC strain are enriched in the Wnt pathway and JNK pathway, which are important pathways regulating melanin production ( Liu et al, 2002 ; Yun et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that changes in H3K4me3 and H3K9me3 fluorescence intensities may have occurred at specific chromatin regions, but they could not be detected by evaluating global nuclear fluorescence intensities. To determine if follicle transition from PA to EA involves changes in H3K4me3 and H3K9me3 levels at specific chromatin sequences, additional studies using ChIP‐seq (Bianco et al, 2019; Mei et al, 2023; Nicol et al, 2018) approaches would be required.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the methylation profiles of T A B L E 2 Percentages of morphologically intact, extruded, and degenerated follicles and antrum formation, mean (± SEM) follicular diameters and daily growth rate in vitro of caprine follicles. additional studies using ChIP-seq (Bianco et al, 2019;Mei et al, 2023;Nicol et al, 2018) approaches would be required.…”
Section: Ros Levels In the Spent Mediummentioning
confidence: 99%
“…These modifications undergo significant age-related changes in oocytes, influencing energy metabolism. Specifically, aging correlates with variations in histone methylation levels and a marked decrease in the expression of histone methyltransferases like lysine acetyltransferase 8 (KAT8), Histone Deacetylase (HDAC), and SIRTs [206,216,[231][232][233][234][235]. Notably, methylation at H3K4 decreases with age in oocytes [206,216,[231][232][233][234].…”
Section: Epigenetic Inheritance Of Energy Metabolism In Aging Oocytesmentioning
confidence: 99%
“…Specifically, aging correlates with variations in histone methylation levels and a marked decrease in the expression of histone methyltransferases like lysine acetyltransferase 8 (KAT8), Histone Deacetylase (HDAC), and SIRTs [206,216,[231][232][233][234][235]. Notably, methylation at H3K4 decreases with age in oocytes [206,216,[231][232][233][234]. The aberrant histone modification, H3.3-K4M, leads to substantial reductions in mtDNA copy number, membrane potential, and ATP content, and escalates ROS levels, along with altering mitochondrial dynamics regulators, oxidative stress-related protein expression, and hydrogen peroxide accumulation [231].…”
Section: Epigenetic Inheritance Of Energy Metabolism In Aging Oocytesmentioning
confidence: 99%